Lupeol, a pentacyclic triterpene, promotes migration, wound closure, and contractile effect in vitro: Possible involvement of PI3K/Akt and p38/ERK/MAPK pathways - Beserra, Fernando Pereira [UNESP]; Xue, Meilang; De Azevedo Maia, Gabriela Lemos; Rozza, Ariane Leite [UNESP]; Pellizzon, Cláudia Helena [UNESP]; Jackson, Christopher John (MDPI, 2018)
Skin wound healing is a dynamic and complex process involving several mediators at the cellular and molecular levels. Lupeol, a phytoconstituent belonging to the triterpenes class, is found in several fruit plants and medicinal plants that have been the object of study in the treatment of various diseases, including skin wounds. Various medicinal properties of lupeol have been reported in the literature, including anti-inflammatory, antioxidant, anti-diabetic, and anti-mutagenic effects. We investigated the effects of lupeol (0.1, 1, 10, and 20 µg/mL) on in vitro wound healing assays and signaling mechanisms in human neonatal foreskin keratinocytes and fibroblasts. Results showed that, at high concentrations, Lupeol reduced cell proliferation of both keratinocytes and fibroblasts, but increased in vitro wound healing in keratinocytes and promoted the contraction of dermal fibroblasts in the collagen gel matrix. This triterpene positively regulated matrix metalloproteinase (MMP)-2 and inhibited the NF-κB expression in keratinocytes, suggesting an anti-inflammatory effect. Lupeol also modulated the expression of keratin 16 according to the concentration tested. Additionally, in keratinocytes, lupeol treatment resulted in the activation of Akt, p38, and Tie-2, which are signaling proteins involved in cell proliferation and migration, angiogenesis, and tissue repair. These findings suggest that lupeol has therapeutic potential for accelerating wound healing.
Keywords: Cell migration; Fibroblasts; Keratinocytes; Lupeol; Wound healing